Controlling the magnetic properties of dysprosium metallofullerene within metal–organic frameworks. Issue 48 (25th November 2016) - Li, Yongjian; Wang, Taishan; Meng, Haibing; Zhao, Chong; Nie, Mingzhe; Jiang, Li; Wang, Chunru
Abstract : The hysteresis and quantum tunneling of magnetism for a metallofullerene DySc2 N@C80 single-molecule magnet were modulated through trapping in MOF-177. Abstract : Magnetic endohedral metallofullerenes represent a new family of single-molecule magnets with a spherical form and solid framework. In this manuscript, we illustrate the controllable quantum tunneling of magnetism for metallofullerene DySc2 N@C80 by means of molecule encapsulation in a porous metal–organic framework (MOF-177) with strong host–guest interactions.